Pengaruh Penambahan Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) terhadap Karakteristrik Jelly Drink - ., Syoufiani; Yusa, Ni Made; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2023)
This study aims to determine the effect of the comparison between red dragon fruit skin extract on the characteristics of jelly drink and to get the right red dragon fruit skin extract ratio to produce jelly drink with the best characteristics. The design used in this study was a completely randomized design with treatment consisting of 5 levels of concentration ratio of red dragon fruit skin extract namely: 20%, 24%, 28%, 32%, dan 36%. Each was repeated 3 times in order to obtain 15 experimental units. The data obtained were analyzed by analysis of variance and the treatment had a significant effect, then followed by the Duncan Multiple Range Test. The result showed that ratio of red dragon fruit skin extract had a significant effect on moisture content, color intensity (l,a,b), scor color, hedonic color, texture, overall acceptance, non significant effect to total anthocyanin, antioxidant capacity, aroma, and taste. The ratio of red dragon fruit skin extract concentrations of 32% produced the best characteristics, moisture content 88.02%, color intensity l* 40.83, a* 58.86, dan b* 33.36, total anthocyanin 0.98 mg/L, antioxidant capacity 9.95 mg GAEAC/100g, color liked and carmine, aroma, texture, taste, overall acceptance is liked.